Influence of tree species on soil properties under different agri-silviculture systems - Gupta, Raj Kumar; Gupta, S. K.; Sehgal, Sandeep (Indian Journal of Agroforestry, 2020)
Agroforestry on croplands is known to be the simple solution for the restoration of soil fertility, especially in the drylands. The present investigation was carried out at the experimental farm of Dryland Research Sub-station, Dhiansar, SKUAST, Jammu during 2014, to study the effect of three agroforestry tree species viz., Albizia lebbeck, Grewia optiva and Leucaena leucocephala on the physical and chemical properties of soil. Physico-chemical analysis of soil at different depths (0-15, 15-30 and 30-45 cm) revealed significant increase in porosity and decrease in bulk density under the tree canopy when compared to control. There was a slight reduction in the soil pH under the tree species. Soil electrical conductivity, in general, was observed to be higher under all the tree species as compared to control. Significant build up of soil organic carbon and available N, P and K in the agri-silviculture system was observed. Out of the three tree species, A. lebbeck had more favourable effect on soil physico-chemical properties. Soil moisture was significantly lower under the tree canopy as compared to control. The soil moisture content, bulk density and pH increased while soil porosity, electrical conductivity, organic carbon and available N, P and K observed decreasing trend with increasing soil depth.